Relationship Between ABCB1 Polymorphisms and Cold Pain Sensitivity Among Healthy Opioid‐naive Malay Males. Issue 7 (22nd February 2017) - Zahari, Zalina; Lee, Chee Siong; Ibrahim, Muslih Abdulkarim; Musa, Nurfadhlina; Mohd Yasin, Mohd Azhar; Lee, Yeong Yeh; Tan, Soo Choon; Mohamad, Nasir; Ismail, Rusli
Abstract: Background: Endogenous and exogenous opioids are substrates of the permeability glycoprotein (P‐gp) efflux transporter, which is encoded by the ABCB1 ( MDR1 ) gene. Genetic polymorphisms of ABCB1 may contribute to interindividual differences in pain modulation and analgesic responses. We investigated the relationship between ABCB1 polymorphisms and cold pain sensitivity among healthy males. Methods: Cold pain responses, including pain threshold and pain tolerance, were measured using the cold‐pressor test (CPT). DNA was extracted from whole blood and genotyped for ABCB1 polymorphisms, including c.1236C>T (rs1128503), c.2677G>T/A (rs2032582), and c.3435C>T (rs1045642), using the allelic discrimination real‐time polymerase chain reaction. Results: A total of 152 participants were recruited in this observational study. Frequencies of mutated allele for c.1236C>T, c.2677G>T/A, and c.3435C>T polymorphisms were 56.6%, 49.7%, and 43.4%, respectively. Our results revealed an association of the CGC/CGC diplotype (c.1236C>T, c.2677G>T/A, and c.3435C>T) with cold pain sensitivity. Participants with the CGC/CGC diplotype had 90% and 72% higher cold pain thresholds (87.62 seconds vs. 46.19 seconds, P = 0.010) and cold pain tolerances (97.24 seconds vs. 56.54 seconds, P = 0.021), respectively, when compared with those without the diplotype. Conclusion: The CGC/CGC diplotype of ABCB1 polymorphisms was associated with variability in cold pain threshold and pain tolerance in healthy males.